Ultrasonicated Membrane Anaerobic System (UMAS) for sewage sludge treatment - Mazza Seddig, Adam Abbakar (2015)
Sewage sludge wastewater causes serious environmental pollution due to its high concentration in term of pollutants. Traditional methods of treating sewage sludge wastewater are disadvantages from both economic and environmental perspectives. In this study, the potentials of Ultrasonic Assisted Membrane Anaerobic System (UMAS) in treating sewage sludge was investigated. The study began with some characterization studies to provide understanding of fundamental issues such as conventional separation, ultrasonic and membrane separations. The aim was to obtain optimum operating conditions, maximum methane production as well as performance of UMAS in treating sewage sludge, upon which further developments on wastewater processes could be developed. A pilot plant scale of UMAS has been used to treat sewage sludge. Different organic loading Rates have been fed to the system, which operated semi continuously at mesophilic temperature and pressure ranges of 1.5 – 2 bar. Seven steady states were attained as a part of a kinetic study that considered concentration ranges of 2670.90 mg/L to 7549.75 mg/L for Mixed Liquor Suspended Solids (MLSS). Kinetic equations from Monod, Contois and Chen and Hashimoto were employed to describe the kinetics of sewage treatment at organic loading rates ranging from 0.904 to 0.952 kg COD/m3/day, throughout the experiment, the removal efficiency of COD was from 90.6 % to 92.78 %. The growth yield coefficient, Y, was found to be 0.391 g VSS/g COD, the specific microorganism decay rate was 0.012 day−1 and the methane gas percentage was between 74 % and 89.64 %. The ammonia and nitrogen removal efficiency were 56-81 % and 56-78 % respectively. The K values were in the range of 0.294 to 0.312 g COD/g VSS/day and μmax values were between 0.287 and 0.312 day−1. The highest color and turbidity removal efficiency were 92.1 % and 96.59 % respectively. The optimum conditions obtained were pH of 6.76 and organic loading rate of 0.90 kg/m3/d, giving a maximum methane production of 87.3 % while the predicted maximum methane percentage was 88 %. The results obtained in this study have exposed the capability of ultrasonic assisted membrane an aerobic system (UMAS) in treating wastewater. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry